Analisis Niat Perilaku Menggunakan Internet Banking di Kalangan Pengguna Internet di Surabaya - Widyarini, Lydia Arie (Jurnal Widya Manajemen & Akuntansi, 2005)
This research describes internet user's acceptance to use internet banking by predicting their behavioral intention to use internet technologies for online banking transaction. Drawing upon both model Technology Acceptance Model and Theory of Planned Behavior (TPB).